Design and ex vivo characterization of narrow implants with custom piezo‐activated osteotomy for patients with substantial bone loss. Issue 3 (31st December 2019) - Wirz, Holger; Teufelhart, Stefan; McBeth, Christine; Gyurko, Robert; Dibart, Serge; Sauer‐Budge, Alexis
Abstract: Objective: Bone augmentation delays implant placement and increases risks due to additional surgeries. Implant systems compatible with reduced alveolar bone volume are required. To design, manufacture, and test a non‐cylindrical dental implant system using piezotomes and custom‐designed matching titanium mini‐implants to address the needs of patients with missing teeth and narrow jawbone. Materials and methods: Tapered mini‐implants with a rectangular cross‐section (4.6 mm × 2.1 mm) were machined with dimensions that could accommodate narrow alveolar ridges. The performance of the implants were tested in both static and fatigue cycle 30° compression tests. Tapered, rectangular cutting tools that matched the overall trapezoidal morphology of the implant were also designed. These novel tools were engineered to be compatible with commercially available piezoelectric osteotomes. Tools were optimized using finite element analysis and were manufactured accordingly and were used by a periodontal surgery team in a pork rib bone model to monitor utility of the device and ease of use. Results: The rectangular design of the implant allows for a full occlusal load due to the larger implant flexural rigidity compared to a similar diameter mini‐implant with a standard cylindrical design. During 30° compression fatigue tests, the implant tested at 340 N did not fail after 5M cycles as shown in Kaplan‐Meier survival curves. Finite element analysis allowed for functional optimization of the roughing and finishing tools. In the pork rib model, these tools successfully cut trapezoidal holes that matched the dimensions of the implant. Conclusions: The implant system here demonstrates the feasibility of a mini‐implant system that has superior flexural rigidity and potentially circumvents the need for patient bone augmentation.